Antonio Cajero Vázquez, El texto y sus contextos: Borges recicla a Borges. El Colegio de San Luis, San Luis Potosí, 2017, 228 pp. - Galván Díaz, Félix Joaquín (El Colegio de México, 2023)
Es una reseña